Die Entwicklung der Beschaftigten in der Chemischen Industrie der Schweiz von 1985 bis 1998 - Neier, Reinhard (My University, 2002)
A graphical representation of the number of people employed by the chemical industry in Switzerland is presented. The number of production sites and the number of persons employed by the chemical industry is relatively small compared to the total number of people in paid employment in Switzerland, however the importance of chemical industry for the Swiss economy is extremely large. Two additional maps show the trends in these figures for 1985-1991 and 1991 -1998. To obtain these data the Swiss Federal Statistical Office has included people working part-time and calculated the full-time equivalents based on the figures obtained by evaluating the number of production sites. This procedure allows numbers to be obtained that are reliable and significant. The geographical distribution is no surprise and shows that the major center of activity is the region of Basel, which is responsible for almost one third of the work places. In addition to the'RegioBasiliensis' the central part of Switzerland between the Lake Constance and Lake Geneva has a relatively high density of chemical industry that is almost evenly distributed. A concentration of chemical industry is also found around the big cities Geneva, Lausanne, and Zurich. In the alpine region there are several major centers of chemical production especially in the cantons Valais and Grisons. The development of the figures of the number of fulltime equivalents between 1985 and 1991 shows some increase in the numbers, whereas between 1991 and 1998 a decrease has occurred. The changes in the chemical industry are in accordance with the general observation of the employment figures for the whole of Switzerland, which reflects the development of the economy during this period. The largest fluctuations are clearly seen in the region of Basel. However one has to take into account that the procedure of counting of production sites attributes one major activity to each independent site and all the employees of one site are then counted as employees of this category. Outsourcing and splitting of activities into different societies may have influenced the results of this evaluation.
Trends in the Number of People Employed by the Swiss Chemical Industry from 1985 to 1998
Keywords: Chemical industry; Number of employees; Statistics; Switzerland